In Vitro Study of Degradation and Cytocompatibility of Ceramics/PLA Composite Coating on Pure Zinc for Orthopedic Application - Su, Shenghui; Tang, Qiangqiang; Qu, Dongbin (Frontiers in Bioengineering and Biotechnology, 2022)
Zinc and its alloys are considered to be next-generation materials for fabricating absorbable biomedical devices. However, cytotoxicity has been reported associated with rapid degradation. To address these issues, a composite coating (PLA/Li-OCP) consisting of CaHPO4∙2H2O conversion coating (Ca-P) and polylactic acid (PLA) decorated with Li-octacalcium phosphate particles were constructed on pure zinc. The immersion tests showed that the presence of Ca-P coating and PLA/Li-OCP coating on pure zinc could reduce the pH value. Compared with Ca-P coating, the introduction of the PLA/Li-OCP film on the Ca-P coated samples could enhance the corrosion resistance, and there was one order of magnitude decrease in the corrosion current density. The cytocompatibility assay suggested that the PLA/Li-OCP coating favored the cell viability and up-regulated the expression of related osteogenic-genes including RUNX2, OCN, and BMP. Therefore, the presence of the PLA/Li-OCP coating on pure zinc could effectively improve the degradation rate and cytocompatibility of pure zinc.